HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHATTERHADAP INSIDEN DIARE PADA ANAK USIA SEKOLAH - Ramona " Apriyanti; Herlina " "; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study has a purpose to determine the relationship of clean and healthy behavior on the incidence of diarrhea in school age children at SDN 181 Pekanbaru. Method of the research that used is correlation descriptive by using Cross Sectional approach. The research was done at SDN 181 Pekanbaru, used 90 samples of students with Proportional Stratified Random Sampling technique in taking the sample, by considering inclusive criteria. Instruments used are questionnaires. Data analyzing used univariat analysis and bivariat analysis by using Chi-Square test. The results of analysis show that 58,9% of students have a clean and healthy life behaviors (PHBS), and 56,7% of students who do not experience diarrhea. The results also indicate that there is relationship between healthy and clean life behavior on the incidence of diarrhea in school age children (p value = (0.001) < α (0.05). Based on the results of this study it is expected for elementary school students to apply clean and healthy life behaviors (PHBS) in school. Key words : School Age Children, Diarrhea, Clean and healthy life behaviors